Odpowiedzi

Najlepsza Odpowiedź!
2009-12-08T15:49:49+01:00
A)(x+7)(2x-1) = 2x²+14x-x-7 = 2x²+13x-7
b)(2a-1)(a+4)= 2a²+8a-a-4 = 2a²+7a-4
c)(4a-1)(2-3a)= 8a-12a²-2+3a =11a-12a²-2
d)(x+√5)(x-√5)=x²-x√5 +x√5-5 = x²-5
e)(2y-√3)(y+1) = 2y²+2y-y√3-√3
f)(a+√2)(a-√3) = a²-a√3+a√2-√6
g)(2√2+k)(√2-k) = 4-2√2k+√2k-k² = 4-√2k - k²
2009-12-08T15:52:34+01:00
A)(x+7)(2x-1) = 2x2[tzn. do potęgi 2] - x + 14x - 7 = 2x2 + 13x - 7
b)(2a-1)(a+4) = 2a2 + 8a - a - 4 = 2a2 + 7a - 4
c)(4a-1)(2-3a) = 8a - 12a2 - 2 + 3a = 11a - 12a2 - 2
d)(x+√5)(x-√5) = x2 - x√5 + x√5 - 5 = x2 - 5
e)(2y-√3)(y+1) = 2y2 + 2y -y√3 - √3
f)(a+√2)(a-√3) = a2 - a√3 + a√2 - √6
g)(2√2+k)(√2-k) = 3√2 - 2k√2 + k√2 -k2
(nie wiem czy dobrze) :)